An active ZnxNi1-xS@Mo2C/carbon cloth electrode as efficient catalyst for water electrolysis. (February 2022) - Shen, Zhiruo; Xu, Changhua; Wang, Sumin; Chen, Jian; Jia, Siqin; Wang, Qiguan
Abstract: Electrolysis of water is a promising method for production of the green-energy hydrogen, which is commonly assisted by high powerful catalyst. At present, developing low-cost and highly efficient electrocatalysts has attracted increasing attention. Herein, a novel composited catalyst of Znx Ni1-x S@Mo2 C loaded on conductive carbon cloth (Znx Ni1-x S@Mo2 C/CC) is successfully prepared by the hydrothermal method. Due to the abundant active sites of defect structures induced by the surface engineering, the prepared Znx Ni1-x S@Mo2 C/CC shows outstanding electrocatalytic performances in hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) of water splitting, with low overpotential of 230 mV and 150 mV at 10 mA cm −2, respectively. The Znx Ni1-x S@Mo2 C/CC as an OER/HER bifunctional catalyst for overall water splitting affords a stable voltage of 1.56 V @current density of 10 mA cm −2 . Moreover, the catalyst shows an outstanding stability after a series of electrochemical tests. This work expands the multi-field applications of carbon cloth-supported materials as efficient non-precious metal-based electrocatalysts, with great importance in sustainable energy-relative technologies. Graphical abstract: Image 1 Highlights: The active Znx Ni1-x S@Mo2 C loaded on carbon cloth (Znx Ni1-x S@Mo2 C/CC) is prepared by a simple hydrothermal method. Excellent electrocatalytic performance in oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is shown. The sample as an OER/HER bifunctional catalyst for full water splitting affords a stable voltage of 1.56 V at 10 mA cm −2 . The prepared Znx Ni1-x S@Mo2 C/CC displays excellent stability.